Cultivating Community Resilience With Agency and Sociality in Gardens for Health and Healing - Budowle, Rachael; Porter, Christine M. (Frontiers in Sustainable Food Systems, 2022)
Communities must develop ever greater resilience as they face the climate emergency and concomitant health and food system challenges. Sustainable food systems research tends to adopt broad and often theoretical social-ecological systems perspectives on resilience. Models theorize that community self-organization for mobilizing change and agency in taking planned action are key processes for community resilience. Empirically, however, how individuals come together to engage in collective action for community resilience remains little explored. In this research, we examine strategies for resilience employed by 19 participants with multiple chronic health conditions in Gardens for Health and Healing, a community-based participatory research project conducted in southeast Wyoming. Through random assignment, participants either received a home garden or designed their own 16-week wellbeing program from a menu of community health and food systems services (e.g., cooking classes, farmers' market gift certificates, home garden). Using a pre-post wellbeing survey, interviews, and 14 months of ethnographic research, we explored the role of choice—or agency—for participants' wellbeing. Survey results suggest that receiving a garden more greatly benefitted participants' physical health while designing and implementing a wellbeing plan more greatly benefitted mental health. Qualitative results find that participants in both the garden and menu conditions identified their intervention as empowering them to take action to improve their own health and wellbeing. Participants attributed their wellbeing less to what condition they were in (garden or menu), and more to the relational processes they engaged in through the project. These processes included bringing the family together; associating with friends, neighbors, and colleagues; caring for garden environments; and engaging with the community-based organization that supported both the gardens and the wellbeing plans. We find that this sociality can help promote and explain a move from individual wellbeing and agency to the collective forms of agency and self-organization necessary to cultivate community resilience for sustainable food systems.